The Lectin Pathway in Thrombotic Conditions—A Systematic Review - Larsen, Julie Brogaard; Hvas, Christine Lodberg; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2018)
The lectin pathway of the complement system can activate the coagulation system in vitro, but the role of the lectin pathway in haemostatic activation and thrombosis in vivo is not clear. We performed a systematic review of the existing literature on associations between the lectin pathway and arterial and venous thrombosis, in accordance with the Assessing the Methodological Quality of Systematic Reviews guidelines. PubMed and Embase were searched from January 1990 to March 2017. We included original studies on human study populations investigating associations between the lectin pathway (protein serum levels, genotype or gene expression) and thrombotic conditions or laboratory coagulation markers. Exclusion criteria were case studies including fewer than five cases, conference abstracts or any other language than English. In total, 43 studies were included which investigated associations between the lectin pathway and cardiovascular thrombotic events (CVEs) (n = 22), ischaemic stroke (n = 9), CVE and stroke (n = 1) and other conditions (systemic lupus erythematosus [n = 6], sepsis-related coagulopathy [n = 3], pulmonary embolism [n = 1], asparaginase treatment [n = 1]). Studies on the lectin pathway and CVE risk reported discrepant results, as both high and low mannose-binding lectin (MBL) serum levels were found to correlate with increased CVE risk. In ischaemic stroke patients, occurrence of stroke as well as increased stroke severity and poor outcome were consistently associated with high serum MBL. For other thromboembolic conditions, only few studies were identified. In conclusion, lectin pathway activation may negatively influence outcome after ischaemic stroke and possibly contribute to CVE risk. Further research is warranted to elucidate the role of the lectin pathway in other thrombotic conditions.
Keywords: lectin pathway; complement proteins; mannose-binding lectin; thromboembolism; blood coagulation